Strategy for art and cultural preservation at Balinese Hindus in praya city, central lombok regency - Widana, I Nyoman Murba (International research journal of management, IT and social sciences, 2017)
This study aimed to review the strategy of cultural preservation among Balinese Hindus in Kota Praya, Central Lombok Regency. This study uses qualitative descriptively in order to find answers the research problems. The focus of this research is the action taken by the people of Bali in Central Lombok in order to preserve the cultural heritage of their ancestors. Based on the results of the study found that the practice of Balinese culture is closely associated with the implementation of the Hindu religion. Associated with it in order to preserve the culture of Bali things to do is to instill religious values to the next generation. Planting religious values, especially done through informal education, non-formal education, and formal education. In connection with the preservation of cultural arts, there are some activities undertaken by people of Bali in Lombok. First, build a gallery of art and culture in order to enhance the creativity of art and culture among the next generation. Second, collaborative art and culture of Balinese and Sasak people in terms of arts and culture to preserve the identity of the cultural arts.